Being a resident of family medicine in Africa in 2019: a picture from the 6th WONCA Africa Conference in Kampala - Ayisi-Boateng, Nana Kwame (2020)
Training young doctors in family medicine is challenging in any setting and many variables can influence the success or failure of a residency program. This article is the end result of a collaborative work that started in June 2019 at the WONCA Africa Regional Conference in Kampala, during a workshop lead by the Besrour Centre for Global Family Medicine at the College of Family Physicians of Canada. We present here the perspective of a small group of young African family physicians on the experience of being a resident in family medicine in Africa in 2019, hoping that the picture we depict here helps to promote the necessary improvements in the training programs in Africa for the near future.